Pengaruh komunikasi dan pemberian insentif terhadap kinerja perawat di RSU Royal Prima Medan - Molek, Molek; Nasution, Sri Lestari Ramadhani; Simbolon, Boyke Marthin (Jurnal Prima Medika Sains, 2019)
Nurse performance is one of the determinants of hospital success rate in providing health services. Efforts to improve nurse performance include paying attention to nurses' work stress. The purpose of this study was to determine the effect of communication and incentives for nurses' performance in the inpatient room at Royal Prima Hospital Medan. This type of cross-sectional research with an explanatory research method approach. The total population of 41 nurses and all nurses used as respondents (total sampling). Data were analyzed using the chi-square test and logistic regression was used to obtain an OR (Odds Ratio) value. The results showed nurses with good communication would increase performance by 6.7 times (p = 0.012: OR = 6.708) and the provision of incentives would increase performance by 6.6 times (p = 0.006; OR = 6.667).